Peningkatan kemampuan pemahaman matematis peserta didik melalui etnomatematika masjid raya Al-Jabar dengan bantuan Geogebra - Susilawati, Wati; Hikmah, Nurul; Hidayah, Rahma Maulida (Papanda Publisher, 2025)
Many students have low mathematical comprehension skills. This is partly due to a loss of interest and desire to learn. The purpose of this study is to improve students' mathematical comprehension skills through an ethnomathematics approach at the Al-Jabbar Grand Mosque with the help of Geogebra. This study, which used a sample of 38 students from SMP IT Ar-Rifqi for the 2024–2025 academic year, examined ethnomathematics in the architecture of the Al-Jabbar Grand Mosque as a geometry teaching aid with the help of Geogebra. Triangles, rhombuses, and other mathematical ideas are reflected in the design of this mosque. This research strategy, which combines exploratory ethnomathematics methodology with a quasi-experimental non-equivalent control group design, uses a quantitative approach. Data collection techniques include pretests and posttests of mathematical comprehension, as well as questionnaires. Data analysis techniques were carried out in several stages, namely the normality test, homogeneity test, unpaired t-test (independent sample t-test), and N-Gain to see the increase in scores from pretest to posttest. The findings of this study indicate that ethnomathematics methods combined with technology (GeoGebra) have significant potential to improve the standards of mathematics teaching. In addition to enhancing conceptual knowledge, this method helps students appreciate their local culture and the practical applications of mathematics